Glioblastoma of pineal region: report of four cases and literature review - Orrego Puelles, Enrique (2017)
We report four cases of glioblastoma in the pineal region. The patients presented a severe headache and vomiting. Brain imaging showed a heterogeneously enhanced tumor in the pineal region with obstructive hydrocephalus. Case 3 developed a subependymal dissemination. The patient went to ventricular-peritoneal shunt and subtotal or total resection and radiotherapy with/without chemotherapy. Cases 1 and 2 received radiation and died 8 and 11 later months. Cases 3 and 4 completed radiotherapy and chemotherapy, and survived 28 and 31 months after the initial diagnosis. Glioblastoma in the pineal region carry a poor prognosis and require neurooncology teams.